The Influence of Parental Attachment to Career Maturity with Self Efficacy as Mediator (Jurnal Bimbingan Konseling, 2018)
This study aims to obtain empirical data and ensure the significance between parental attachment and analyze self efficacy as a mediation variable on career maturity. The research design used is correlational research design with a sample of 323 students selected by using sample random sampling technique. Data collection using the Inventory of Parent and Peer Attachment (IPPA) instruments, Career Decision Self Effiacy Scale-Short Form (CDSE-SF), and Career Maturity Scale. The mediator analysis technique uses corrected bootstrap method (N = 5000) with 95% confidential interval in PROCESS software. The results showed that Parental attachment through self efficacy has an influence on career maturity. The conclusion is that parental attachment has a significant indirect effect on career maturity